Processing math: 0%

Thursday, May 28, 2015

2015/052) Find four numbers in A.P. whose sum is 20 and sum of whose squares is 120?

without loss of generality we can choose numbers to be a - 3d, a - d, a + d, a-3d and d > 0

now sum = (a-3d) + (a-d) + (a+d) + (a+3d) = 4a = 20 or a=5

sum of squares = (a-3d)^2 + (a- d)^2 + (a+d)^2 + (a+3d)^2 = 4a^2 + 20d^2 = 120

so putting value of a we get d = 1 so numbers are 2,4,6,8
I found the problem at https://in.answers.yahoo.com/question/index?qid=20150528071206AAbn3Cz



Monday, May 25, 2015

2015/051)If m\tan(a-30^\circ)=n\tan(a+120^\circ) show that \cos2a=\dfrac{m+n}{2(m-n)}



we have \tan (a+ 120^\circ) = - \cot(a + 30^\circ) using \tan (x+90^\circ) = - cot\, x
so mtan(a-30^\circ)= -n \cot ( a+ 30^\circ)
so \tan (a+30^\circ) tan (a-30^\circ) = - \dfrac{n}{m}
\dfrac{\tan\, a + \tan\, 30^\circ}{1- \tan\, a \tan\, 30^\circ}\dfrac{tan\, a -\tan\, 30^\circ}{1 + \tan\, a \tan\, 30^\circ} = -\dfrac{n}{m}
or \dfrac{\tan ^2 a - \tan ^2 30^\circ}{1- \tan ^2 a \tan ^2 30^\circ} = -\dfrac{n}{m}


or \dfrac{\tan ^2 30^\circ-\tan ^2 a}{1- \tan ^2 a \tan ^2 30^\circ} = \dfrac{n}{m}

or \dfrac{\frac{1}{3}-\tan ^2 a}{1- \frac{1}{3}\tan ^2 a} = \dfrac{n}{m}


 or \dfrac{1-3 \tan ^2 a}{3- \tan ^2 a} = \dfrac{n}{m}

  using componendo dividendo to get

\dfrac{4 - 4 \tan ^2 a}{- 2 - 2 \tan ^2 a} = \dfrac{n+m}{n-m}

or 

2 \dfrac{1 - 1 \tan ^2 a}{1 + \tan ^2 a} = \dfrac{n+m}{m-n}

or 

2 \dfrac{1 - \tan ^2 a}{sec ^2 a} = \dfrac{n+m}{m-n}

or

2 (1 - \tan ^2 a)(cos ^2 a) = \dfrac{n+m}{m-n}

 or (\cos^2 a-\sin ^2 a) = \dfrac{m+n}{2(m-n)}
or \cos 2a = \dfrac{m+n}{2(m-n)}


Friday, May 15, 2015

2015/050) If ax + y + 1= 0, x +by+1=0, x+y+c=0

are concurrent then prove that \dfrac{1}{1-a} + \dfrac{1}{1-b} + \dfrac{1}{1-c} = 1

proof

We have
a = - \dfrac{y+1}{x}
or 1- a = \dfrac{x+y+1}{x}
or \dfrac{1}{1-a} = \dfrac{x}{x+y + 1} \cdots 1

similarly

x +by+1=0
=> x+1 = - by
or b = -\dfrac{x+1}{y}
or 1-b= \dfrac{x+y+1}{y}
or \dfrac{1}{1-b} = \dfrac{y}{x+y+1}\cdots (2)

and x+y+c=0
=> -c = x + y
=> 1-c = x+y+1
or \dfrac{1}{1-c} = \dfrac{1}{x+y+1}\cdots(3)

adding all 3 we get the
\dfrac{1}{1-a} + \dfrac{1}{1-b} + \dfrac{1}{1-c} = \dfrac{x+ y + 1}{x+y+1} =1

Proved 


Thursday, May 14, 2015

2105/049) For what positive integral values of x is 3^x-x^2 is divisible by 5

As 3 and 5 are coprimes

So 3^4 = 1 mod 5
3^{4k+1} = 3 mod 5
3^{4k+2}= 4 mod 5
3^{4k+3} = 2 mod 5


Now (5k+m)^2 mod 5 = 0 if m= 0, 1 if m= 1 or 4, 4 if m = 2 or 3 mod 5

now 3^x= x^2 mod 5 if

x = 4k that is 0 mod 4 and 1 mod 5 ( in both cases remainder 1)
or x = 4k and 4 mod 5( in both cases remainder 1)
or x = 4k+2 or 2 mod 4 and 2or 3 mod 5
x = 0 mod 4 and 1 mod 5 => x= 16 mod 20
or x = 4k and 4 mod 5 => x = 4 mod 20

or x =2 mod 5 and 2 mod 4 => x = 2 mod 20

or x = 2 mod 4 and 3 mod 5 => x= 18 mod 20

x = a mod 4 ,b mod 5 can be solved by Chinese remainder theorem
I have not detailed steps


Tuesday, May 12, 2015

2015/048) What could be possible value of integer a if 10^ {2n +1} + a.7^ {2n +1} is divisible by 51 exactly

we have 10^2 = 100 = -2 mod 51

so 10^ {2n +1} = 10(-2)^n

7^2 = -2 mod 51

so a.7^ {2n +1} = 7a (-2)^n mod 51

10^{2n +1} + a.7^ {2n +1} mod 51
= 10(-2)^n  + 7a (-2)^n = 0 as divisible by 51

so 10 + 7a = 0 mod 51
7a = - 10 mod 51 = 41 mod 51

7a = 41 mod 51

we need to find inverse of 7 mod 51( we can find by extended euclid algorithm as below)

51 = 7 * 7 + 2  or  2 = 51- 7 * 7

7 = 2 * 3 + 1 or 1= 7 - 2 * 3 = 7 - (51- 7 * 7) * 3 = 51 * 3 - 22 * 7

so 22 = inverse of 7 mod 51

so a = 41 * 22 mod 51 or 35 mod 51 or 51k + 35


 

Sunday, May 10, 2015

2015/047) Prove that if x = log_a(bc),y = log_b(ca),z = log_c(ab) then the value of xyz - x - y - z is 2


we have
x= log_a(bc)

so 1 + x = 1 + log_a(bc) = log_a(a) + log_a(bc) = log_a(abc)

or \dfrac{1}{1+x} = log_{abc}(a) \cdots (1)

similarly
\dfrac{1}{1+y} = log_{abc}(b) \cdots (2)
\dfrac{1}{1+z} = log_{abc}(c) \cdots (3)
 
 Adding (1), (2) and (3) we get
\dfrac{1}{1+x}+ \dfrac{1}{1+y}+ \dfrac{1}{1+z} = log_{abc}(a) + log_{abc}(b) + log_{abc}(c) = log_{abc}(abc) = 1

or
(1+y)(1+z) + (1+z)(1+x) + (1+x)(1+y) = (1+x)(1+y)(1+ z)

or

1 + yz + y + z + 1 + xz + x + z + 1 + xy + x + z = 1 + x + y + z + xy + yz + zx + xyz

or 2 + x + y+ z = xyz

or xyz – x – y -z = 2

2015/046) Prove that for any natural number n, 11^{n + 2} + 12^{2n + 1} is divisible by 133


we have

11^{n + 2} + 12^{2n + 1}

= 11^2 * 11 ^n + 12 * 12^{2n}

= 121 * 11^n + 12 * 144^n

= 121 * 11^n + 12 * 11^n + 12 * 144^n – 12 * 11^n

= 133 * 11^n + 12( 144^n – 11^n)

the 1st term is multiple of 133 and 2nd term is divisible by 144-11 ( a^n-b^n) is divisible by a – b and hence the sum.

Friday, May 8, 2015

2015/045) Factor 5x^2-48x-20

Let us take product of 5 and - 20 (coefficient of x^2 and constant)
that is - 100
find -48 and sum of 2 number so that product is -100 ( - 50 and 2 by trial and error). take factors of 100 and find sum
so 5x^2 - 48 x - 20
= 5x^2 - 50 x + 2x - 20 now by grouping
= 5x(x-10) + 2(x - 10)
= (5x+2)(x-10)

Sunday, May 3, 2015

2015/044 ) If x=1+log_a(bc) ,y=1+log_b(ca) ,z=1+log_c(ab) then, show that xyz=xy+yz+zx

we have x = log_a a + log_a(bc) = log_a (abc)

or \dfrac{1}{x} = log_{abc} (a) \cdots  (1)

y = log_b b + log_b(ca) = log_b (abc)

or \dfrac{1}{y} = log_{abc} (b) \cdots(2)

z = log_c c + log_c(ab) = log_c (abc)

or \dfrac{1}{z} = log_{abc} (c) \cdots (3)

add (1) (2) and (3) to get

\dfrac{1}{x}  +\dfrac{1}{y} + \dfrac{1}{z} = log_{abc} (a) + log_{abc} (b) + log_{abc} (c) = log_{abc} (abc) = 1

or \dfrac{1}{x}  +\dfrac{1}{y} + \dfrac{1}{z}=1

multiplying both sides by xyz we get

yz + zx + xy = xyz


proved


this problem I picked from  https://in.answers.yahoo.com/question/index?qid=20150503005943AArBg7a

2015/043) Find the integer part of 1 + \dfrac{1}{\sqrt{2}}+ \dfrac{1}{\sqrt{3}}+ \dfrac{1}{\sqrt{4}}+ \cdots+ \dfrac{1}{\sqrt{1000000}}

note that \dfrac{1}{\sqrt{k}} = \dfrac{2}{2 \sqrt{k}}= \dfrac{2}{\sqrt{k}+ \sqrt{k}}

now

 \dfrac{2}{\sqrt{k}+ \sqrt{k}}\lt \dfrac{2}{\sqrt{k}+ \sqrt{k-1}}\lt 2(\sqrt{k}- \sqrt{k-1})
adding from k = 2to n we get sum \lt 2(\sqrt{n}-1) or \lt 1998 (when n= 10^6)

adding 1 we get sum = 1999

again
\dfrac{2}{\sqrt{k}+ \sqrt{k}}\gt \dfrac{2}{\sqrt{k}+ \sqrt{k+1}}\gt 2(\sqrt{k+1}- \sqrt{k})

 adding sum from 2 to n we get \gt 2(\sqrt{n+1} - \sqrt{2}) \gt 1997

so sum from 1 > 1998

so integer part of sum = 1998

2015/042) If roots of the equation x^4 - 8x^3 + bx^2 +cx +16 =0 are positive ,then?

a) b=8=c
b)c= -32, b=28
c)b=24,c= -32
d)c=32, b=24


Product = 16 and sum = 8 and all are >0

they are 2,2,2,2 other combinations for example (1,1,1,16) , (1,1,2,8) do not give sum 8

so the expression is (x-2)^4

= x^4-8x^3 + 24x^2 - 32x + 16

hence b = 24 and c = - 32

Friday, May 1, 2015

2015/041) Show that if square root of an integer is not integer then it is irrational


Let the number be r and square root be rational and not ain integer let it be \dfrac{p}{q} where gcd(p,q) = 1 that is it is in lowest form
\sqrt{r}= \dfrac{p}{q}
so
p = q\sqrt{r}\cdot(1)
and
p\sqrt{r}= qr \cdot(2)
as gcd(p,q) =1 there exists m and n as per Bezout Identity such that
mp + nq = 1
so \sqrt{r} = \sqrt{r}.1= \sqrt{r}(mp+nq) =mp\sqrt{r} + nq\sqrt{r} = mqr + np
which is integer.
this leads to contradiction and hence it is irrational.